Influence of the environment on the surface conductivity of chemical vapor deposition diamond - Foord, J; Lau, C; Hiramatsu, M; Jackman, R; Nebel, C; Bergonzo, P (2002)
The influence of differing chemical environments on the surface conductive properties of chemical vapor deposition (CVD) diamond films has been explored. Only small changes in the insulating character of the diamond surface is observed when surfaces freshly hydrogenated in a microwave plasma are exposed in-situ to water vapour or a range of common gases in separate experiments. However, a large increase in surface conductivity is seen if the surface is first exposed to water vapour and then other gasses including oxygen, carbon dioxide and formic acid. Conductivity changes are also observed in solution of differing pH, although irretrievable loss of the conductive phase is observed if the diamond is heated in alkaline solution. The applicability of recent models in explaining the observations is considered. © 2002 Elsevier Science B.V. All rights reserved.